2023
DOI: 10.1002/ctm2.1386
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐associated macrophages in gastric cancer: From function and mechanism to application

Jie Li,
Juan Sun,
Ziyang Zeng
et al.

Abstract: BackgroundGastric cancer (GC) is a malignant tumour, with high morbidity and mortality rates worldwide. The occurrence and development of GC is a complex process involving genetic changes in tumour cells and the influence of the surrounding tumour microenvironment (TME). Accumulative evidence shows that tumour‐associated macrophages (TAMs) play a vital role in GC, acting as plentiful and active infiltrating inflammatory cells in the TME.Main bodyIn this review, the different functions and mechanisms of TAMs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 173 publications
(472 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that infiltration of naive B cells in GC is associated with an unfavorable prognosis 34 . It is widely acknowledged that excessive activation of M2 macrophages can contribute to fibrosis during tissue healing and possibly encourage tumor development via immunosuppression 35 . In this research, we investigated the positive correlation between the expression of naive B cells and TIE1, and we further observed higher levels of M2 macrophages and lower levels of M1 macrophages in GC patients with elevated TIE1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that infiltration of naive B cells in GC is associated with an unfavorable prognosis 34 . It is widely acknowledged that excessive activation of M2 macrophages can contribute to fibrosis during tissue healing and possibly encourage tumor development via immunosuppression 35 . In this research, we investigated the positive correlation between the expression of naive B cells and TIE1, and we further observed higher levels of M2 macrophages and lower levels of M1 macrophages in GC patients with elevated TIE1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…TAMs-targeted treatment is an optimizing strategy to improve the therapeutic effect of anti-tumor immunotherapy. [71][72][73][74] In this section, we discussed the effects of PDE5 inhibitors on macrophages in TME (Table 2). 67,68,69 The effects of PDE5 inhibitors depend on the different polarization status of macrophages.…”
Section: Macrophagesmentioning
confidence: 99%
“…Gastric carcinoma is the third deadliest type of cancer [4]. Its pathogenesis is complex and closely related to age, high salt intake and a lack of fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%